Modern forests : statemaking and environmental change in colonial eastern India - Sivaramakrishnan, K. (Studies in social ecology and environmental history, 1999)
Modern Forests is an environmental, institutional, and cultural history of forestry in colonial eastern India. By carefully examining the impact of regional political formations and biogeographic processes on land and forest management, this book probes the interrelated social and biophysical factors that influenced landscape change. Through a cultural analysis of powerful landscape representations, Modern Forests reveals the contention, debates, and uncertainty that persisted for two hundred years of colonial rule as forests were identified, classified, and brought under different regimes of control and were transformed to serve a broad array of imperial and local interests."--BOOK JACKET.